Exploring Community-Based Intervention as a Response to the Sing Beling Sing Nganten Phenomenon in Bali - Sarasvati, Hita Lafia; Hiryanto; Wangid, Muhammad Nur (JPPM (Jurnal Pendidikan dan Pemberdayaan Masyarakat), 2025)
The phenomenon of “sing beling sing nganten” is literally translated as “no pregnancy, no marriage”, and reflects the normalization of premarital pregnancy as a social strategy to legitimize relationships and secure familial approval. Rooted in value in Bali, this practice disproportionately impacts women, compromising their reproductive autonomy, psychological well-being, and social status. Although early initiatives such as education and empowerment programs have emerged, evidence of effective interventions specifically addressing this issue remains limited. This study conducted a systematic literature review to explore community-based interventions (CBI) targeting related issues, including gender inequality, reproductive rights, fertility pressure, domestic violence, and early marriage. Of 131 records screened across databases and journals, 22 articles were included. The studies, spanning Africa, Asia, and Latin America, employed randomized controlled trials, quasi-experiments, qualitative designs, and mixed methods, involving participants ranging from adolescents to socioeconomically vulnerable women and men. Research findings highlight that CBI delivered through participatory group sessions, school programs, home visits, and community dialogues can effectively reshape gender norms, strengthen reproductive health knowledge, increase men’s engagement, and reduce violence. Key success factors include a multilevel approach involving families, schools, community leaders, health care providers, and policy structures. The review concludes that adapting evidence-based CBI to the Balinese cultural context offers a promising pathway to addressing sing beling sing nganten. The review emphasizes the need for context-sensitive, participatory, and gender-transformative strategies to ensure sustainable change in social norms and to protect women’s rights. Keywords: sing beling sing nganten, community-based intervention, premarital pregnancy, gender norms